Dendritic Core‐Frame and Frame Multimetallic Rhombic Dodecahedra: A Comparison Study of Composition and Structure Effects on Electrocatalysis of Methanol Oxidation. Issue 1 (3rd November 2017) - Mathurin, Leanne E.; Tao, Jing; Xin, Huolin; Li, Jun; Zhu, Yimei; Chen, Jingyi
Abstract: The composition and structure of multimetallic nanostructures can be tailored to enhance electrocatalytic properties. This work reports a seed‐mediated synthesis of novel multimetallic dendritic core‐frame and frame nanostructures with a rhombic dodecahedral shape for enhanced methanol oxidation reaction (MOR). The synthesis involves in situ formation of Cu seeds and the subsequent selective deposition of Pt and Ru on the edges and vertices of the Cu seeds to generate CuPt and CuPtRu dendritic core‐frame nanostructures. The core‐frame nanostructures undergo a post acetic acid etching process to form the frame nanostructures. While transmission electron microscopy reveals the morphology and elemental distribution of the nanostructures, X‐ray diffraction patterns confirm the alloy compositions of dendritic frames for both the core‐frame and frame nanostructures. Compared to the bimetallic CuPt nanostructures, the trimetallic CuPtRu nanostructures lower the onset potential and completely suppress the peak current in the reverse scan for MOR. The CuPtRu alloyed frame nanostructures are the best to prevent Ru leaching compared to the CuPtRu core‐frame nanostructures and PtRu catalysts. X‐ray photoelectron spectroscopy reveals that all three elements become more electron rich in the frame nanostructures. Further refining the composition ratio of the CuPtRu alloyed dendritic frame nanostructures can lead to more efficient catalysts at a lower cost for MOR. Abstract : Multimetallic dendritic core‐frame and frame nanostructures with a rhombic dodecahedral shape were developed for enhanced methanol oxidation reaction. Compared to the bimetallic CuPt nanostructures, the trimetallic CuPtRu nanostructures lower the onset potential and completely suppress CO poisoning. The CuPtRu alloyed frame nanostructures are the best to prevent Ru leaching compared to the CuPtRu core‐frame nanostructures and PtRu catalysts.